المشترك اللفظي وترجمة معانية في سورة البقرة : دراسة تحليلية " فيمفينن الرحمن " أنموزجا - Zafirah 'Afifah Ahmad Lotpi (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2021)
It is known that the polysemy in the Qur'an indicates several meanings, but it is not permissible to understand the meaning of another place, otherwise the total significance of the verse is deviated. This research aims to study the polysemy in Arabic and its effect on the interpretation of the Qur'an in Malay, known as "The Interpretation of Pimpinan al-Rahman". The researcher chose Surah al-Baqarah because it is the longest surah of the Qur'an, by employing the descriptive approach in collecting information, the analytical approach in discussing it, as well as collecting information from a number of sources, including interpretations, dictionaries and social sites on the internet, in order to know the meaning of the polysemy among scholars and its statement in the Qur'an by extracting the meanings, in order to analyze its translation from "Interpretation of Pimpinan al-Rahman". It also investigates the extent of its polysemy consideration, and thus, the research is interested in enriching the Arabic and Malay previous studies by studying the polysemy and its application in the Qur'an, as well as helping to understand the Qur'anic vocabulary accurately, maintaining the soundness of the meaning from distortion and misunderstanding, and urging the community to read interpretation books in Malay.